PENGARUH KOMUNIKASI LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PELAYANAN PERIZINAN TERPADU PROVINSI RIAU - Musdaleni Musdaleni (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
Since the 20th century, with the increasing flow of globalization in all aspects of organizational life, the competitiveness of organizations has increased in speed and complexity and has resulted in an increase in the competitiveness of individual and group work within the organization. Individuals who excel will win the competition. As explained by Ulrich (1997: 98) explains that the flow of globalization has resulted in competition between organizations and companies running as a whole. This competition is getting more open because it is coupled with changes in global technology and changes in organizational culture rapidly. These changes are difficult to control without optimizing the individual performance and technological developments of each organization. The value of respondents' responses to the work environment can be said to be relatively large, but when compared to the value of respondents' responses from the education and training variables, the work environment has the smallest value. This can happen because respondents are still hesitant in answering statements about the work environment. Because the assessment of the work environment that still does not have their respective benchmarks. So the resulting answer is also not too high. This of course affects the results of research on the influence of the work environment on employee performance. Respondents may assume that the work environment has no significant effect on improving employee performance as long as the employee has a good quality of education and training that has been followed.